2019
DOI: 10.1111/ffe.13182
|View full text |Cite
|
Sign up to set email alerts
|

Minimum fatigue striation spacing and its stress amplitude dependence in a commercially pure titanium

Abstract: We report the fatigue striation spacing of commercially pure titanium with respect to stress amplitude. Rotating bending fatigue tests were performed at 150, 175, 200 and 227 MPa in which samples did not fail at 150 MPa. No fatigue striation up to a certain crack length is observed for the studied conditions. For each condition, a minimum striation spacing value is found that decreases from 0.45 to 0.36 to 0.24 μm with increasing stress from 175 to 200 to 227 MPa, respectively. The minimum striation spacing re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, Ahmed et al. [7] reported that striation spacing increased when the stress decreased for commercially pure titanium. They illustrated that the threshold crack length was 2.5, 1.9, and 1.4 mm, where striation spacing started to increase at 175, 200, and 227 MPa, respectively [7] .…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Ahmed et al. [7] reported that striation spacing increased when the stress decreased for commercially pure titanium. They illustrated that the threshold crack length was 2.5, 1.9, and 1.4 mm, where striation spacing started to increase at 175, 200, and 227 MPa, respectively [7] .…”
Section: Data Descriptionmentioning
confidence: 99%
“…They illustrated that the threshold crack length was 2.5, 1.9, and 1.4 mm, where striation spacing started to increase at 175, 200, and 227 MPa, respectively [7] . The related minimum value for striation spacing was also reported as 0.45, 0.36, and 0.24 µm, for the mentioned applied stress [7] .
Fig.
…”
Section: Data Descriptionmentioning
confidence: 99%
“…As a material with high specific strength, good corrosion resistance and many other excellent characteristics, 1,2 commercial pure titanium (CP‐Ti) is widely used in aviation and chemical equipment fields. Many fatigue failures of piping and vessels manufactured with CP‐Ti were reported under a variety of different conditions of cyclic loading 3–6 .…”
Section: Introductionmentioning
confidence: 99%